2022
DOI: 10.3390/antiox11071392
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Neuroprotective Effects of Paeonol against Oxidative Stress and Altered Carrier-Mediated Transport System on NSC-34 Cell Lines

Abstract: Paeonol is a naturally occurring phenolic agent that attenuates neurotoxicity in neurodegenerative diseases. We aimed to investigate the antioxidant and protective effects of paeonol and determine its transport mechanism in wild-type (WT; NSC-34/hSOD1WT) and mutant-type (MT; NSC-34/hSOD1G93A) motor neuron-like amyotrophic lateral sclerosis (ALS) cell lines. Cytotoxicity induced by glutamate, lipopolysaccharides, and H2O2 reduced viability of cell; however, the addition of paeonol improved cell viability agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 72 publications
(95 reference statements)
0
4
0
Order By: Relevance
“…Eugenol scavenges free radicals by donating the phenolic hydroxyl group [23]. Much literature is unavailable on TMA, but Paeonol (2 -Hydroxy-4 -methoxyacetophenone), a structurally similar compound to TMA, has shown neuroprotection in vivo and in vitro by reducing oxidative stress [64,65]. A previous study suggested that eugenol, being lipophilic, influences the redistribution of protons across the membrane, thereby affecting membrane potential [66].…”
Section: Discussionmentioning
confidence: 99%
“…Eugenol scavenges free radicals by donating the phenolic hydroxyl group [23]. Much literature is unavailable on TMA, but Paeonol (2 -Hydroxy-4 -methoxyacetophenone), a structurally similar compound to TMA, has shown neuroprotection in vivo and in vitro by reducing oxidative stress [64,65]. A previous study suggested that eugenol, being lipophilic, influences the redistribution of protons across the membrane, thereby affecting membrane potential [66].…”
Section: Discussionmentioning
confidence: 99%
“…The anesthetic isoflurane has neurotoxicity, and its long-term use in the developing brain will lead to cognitive impairment and memory impairment (Culley et al, 2004;DiMaggio et al, 2011) et al, 2022). Similarly, it improves amyotrophic lateral sclerosis by reducing glutamate levels to inhibit oxidative stress (Latif et al, 2022).…”
Section: Othersmentioning
confidence: 99%
“…It mainly upregulates MDA, ROS, and TNF‐α and downregulates GSH and SOD levels in the hippocampus to reduce oxidative stress and inflammatory response and at the same time reduces neutrophil infiltration (Pourmohammadi et al, 2022). Similarly, it improves amyotrophic lateral sclerosis by reducing glutamate levels to inhibit oxidative stress (Latif et al, 2022). It alleviates dry skin pruritus and reduces the expression of Chemokine C‐X‐C‐Motif receptor 3 (CXCR3) in spinal cord neurons, thus inhibiting the activation of astrocytes (Wang et al, 2021).…”
Section: Protective Effect Of Pae On Cnsmentioning
confidence: 99%
“…Paeonol, chemically known as 2-hydroxy-4-methoxy acetophenone, and the chemical structures are presented in Figure 1 . It has a low molecular weight of 166.17 g/mol and a melting point of 52°C ( Latif et al, 2022 ). It has been found to exert antitumor effects through various molecular mechanisms ( Fu et al, 2018 ; Cai et al, 2020 ; Zhang et al, 2020a ).…”
Section: Pharmacological Properties Of Paeonolmentioning
confidence: 99%